2010
DOI: 10.7498/aps.59.2240
|View full text |Cite
|
Sign up to set email alerts
|

Time delay to enhance the giant suppression in a bistable system

Abstract: Effects of time delay on the active rate of a bistable system was investigated. Using the steepest-descent approximation method, the analytical expression of the mean first passage time and the active rate of the bistable system with time delay was derived under the condition of small delay time. The numerical computations show that the time delay enhances the resonance suppression in the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Consider a bistable system with global delay and subjected to correlated multiplicative and additive noises: [38]…”
Section: The Case For the Bistable System With Global Delaymentioning
confidence: 99%
See 1 more Smart Citation
“…Consider a bistable system with global delay and subjected to correlated multiplicative and additive noises: [38]…”
Section: The Case For the Bistable System With Global Delaymentioning
confidence: 99%
“…For a bistable system where the time delay exists in linear and cubic terms simultaneously, its stationary properties and rate process are given by a small delay expansion. [38] It is indicated that the transition rate and the mean first passage time both follow Arrhenius' law when the additive noise intensity is small, even if the delay is large. In order to fully understand the dynamical properties of the stochasticdelayed system, the correlation function of state variable should be further considered.…”
Section: Introductionmentioning
confidence: 99%